Negligible contribution of bone marrow-derived cells to collagen production during hepatic fibrogenesis in mice. - Higashiyama, R; Moro, T; Nakao, S; Mikami, K; Fukumitsu, H; Ueda, Y; Ikeda, K; Adachi, E; Bou-Gharios, G; Okazaki, I; Inagaki, Y (2009)
BACKGROUND and AIMS: Recent studies have reported that bone marrow (BM)-derived cells migrating into fibrotic liver tissue exhibit a myofibroblast-like phenotype and may participate in the progression of liver fibrosis. However, their contribution to collagen production has not been fully verified yet. We revisited this issue by using 2 mechanistically distinct liver fibrosis models introduced into transgenic collagen reporter mice and their BM recipients. METHODS: BM of wild-type mice was replaced by cells obtained from transgenic animals harboring tissue-specific enhancer/promoter sequences of alpha2(I) collagen gene (COL1A2) linked to enhanced green fluorescent protein (EGFP) or firefly luciferase (LUC) gene. Liver fibrosis was introduced into those mice by repeated carbon tetrachloride injections or ligation of the common bile duct. Activation of COL1A2 promoter was assessed by confocal microscopic examination detecting EGFP signals and luciferase assays of liver homogenates. RESULTS: The tissue-specific COL1A2 enhancer/promoter was activated in hepatic stellate cells following a single carbon tetrachloride injection or during primary culture on plastic. A large number of EGFP-positive collagen-expressing cells were observed in liver tissue of transgenic COL1A2/EGFP mice in both liver fibrosis models. In contrast, there were few EGFP-positive BM-derived collagen-producing cells detected in fibrotic liver tissue of COL1A2/EGFP recipients. Luciferase assays of liver tissues from COL1A2/LUC-recipient mice further indicated that BM-derived cells produced little collagen in response to fibrogenic stimuli. CONCLUSIONS: By using a specific and sensitive experimental system, which detects exclusively BM-derived collagen-producing cells, we conclude an unexpectedly limited role of BM-derived cells in collagen production during hepatic fibrogenesis.